Impact of mulch on weed infestation in System of Rice Intensification (SRI) farming - Wayayok, Aimrun; Mohd Soom, Mohd Amin; Abdan, Khalina; Mohammed, Umar (Elsevier, 2014)

(untitled)
Weeds infestation is one of the major constrains of SRI due to wide planting geometry and moist environment, thereby reducing rice yield up to 69.15%. This study aimed at evaluating the effect of two mulching materials (rice straw SRImats and plastic) on management of weed infestation, and determining of seedling behaviour. The parameters used for the analysis of weeds were density, relative density, dry weight, relative dry weight, summed dominance ratio and control efficiency. The results revealed that weed density was significantly reduced with range from control plot (1950.67 No.) to the rice straw SRImats plot (33.00 No.).